2020
DOI: 10.1186/s12885-020-07555-0
|View full text |Cite
|
Sign up to set email alerts
|

Verteporfin inhibits cell proliferation and induces apoptosis in different subtypes of breast cancer cell lines without light activation

Abstract: Background Breast cancer (BC) can be divided into five subtypes: Lumina1A, Lumina1B, HER-2 overexpression, Basal-like and Normal breast-like subtype, based on the differently expressed genes in breast cancer tissue. The Hippo signaling pathway plays an indispensable role in BC. The YAP gene is a terminal effector of Hippo pathway, and hyperactivation of YAP mediates tumorigenesis. As an inhibitor of YAP, non-photoactivated verteporfin (VP) can inhibit YAP-mediated tumor proliferation and angiogenesis by elimin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 34 publications
3
28
0
Order By: Relevance
“…YAP not only activates ERK and AXL signaling, but also induces epithelial–mesenchymal transition (EMT) against EGFR-TKI treatment [ 16 ]. Several studies have shown that YAP inhibition can overcome resistance to chemotherapy [ 39 , 40 , 41 , 42 ]. For example, the combined treatment of EGFR-TKI with YAP inhibitors suppresses EGFR-TKI resistance [ 16 ].…”
Section: The Role Of Yap In Chemo-resistance and Metastasismentioning
confidence: 99%
“…YAP not only activates ERK and AXL signaling, but also induces epithelial–mesenchymal transition (EMT) against EGFR-TKI treatment [ 16 ]. Several studies have shown that YAP inhibition can overcome resistance to chemotherapy [ 39 , 40 , 41 , 42 ]. For example, the combined treatment of EGFR-TKI with YAP inhibitors suppresses EGFR-TKI resistance [ 16 ].…”
Section: The Role Of Yap In Chemo-resistance and Metastasismentioning
confidence: 99%
“…This drug is used as a photosensitizer for photodynamic therapy to eliminate abnormal blood vessels in the eye, which are associated with conditions such as the wet form of macular degeneration [ 19 ]. Recently, verteporfin has also been shown to inhibit the function of the oncogene YAP1 through regulation of YAP1 SUMOylation, proposing verteporfin for clinical use to treat breast cancer [ 20 ], as well as myeloma [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…This drug is used as a photosensitizer for photodynamic therapy to eliminate abnormal blood vessels in the eye, which are associated with conditions such as the wet form of macular degeneration [19]. Recently, verteporfin has also been shown to inhibit the function of the oncogene YAP1 through regulation of YAP1 SUMOylation, proposing verteporfin for clinical use to treat breast cancer [20], as well as myeloma [21]. The process of identifying the most active individual compounds was then repeated for plate 10 (Figure 2D,E), resulting in the identification of compound P10G08 as the most potent inhibitor of the pUL50-pUL53 interaction (IC 50 = 38 nM, Figure 2F).…”
Section: Identification Of Hcmv Core Nec Inhibitors From the Prestwick Chemical Library ®mentioning
confidence: 99%
“…Effects of paclitaxel on apoptosis and the apoptosis signaling pathways in PC9 cells. Chemotherapy drugs can inhibit cell proliferation and induce apoptosis in human cancer cells (36)(37)(38). To confirm that the cell death caused by paclitaxel was indeed apoptosis, we performed Annexin V and PI staining for a flow cytometry analysis.…”
Section: Effects Of Paclitaxel On Mmpmentioning
confidence: 99%